Strategi Reintegrasi Sosial UPT P2TK Disnakertrans Jawa Timur dalam Mengatasi PMI Deportasi dari Malaysia - Chelsa Aulia F.; Wahidah Zein Br. Siregar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Working abroad has become a choice for many residents of East Java to improve their families’ economic conditions, with Malaysia as the main destination. However, the phenomenon of deportation particularly through non-procedural channels gives rise to complex issues ranging from economic hardship and psychological trauma to negative stigma in their communities of origin, which can hinder social reintegration. This study aims to examine the social reintegration strategies implemented by the UPT P2TK of the East Java Provincial Department of Manpower and Transmigration for deported Indonesian migrant workers (PMI) from Malaysia, as well as to identify the barriers and effectiveness of these interventions. The research method employed is qualitative with a descriptive approach. Data were collected through observation, documentation, and in-depth interviews with informants at the UPT P2TK from February to April 2026. The findings indicate that the UPT P2TK has implemented reintegration strategies through stages of stabilization at shelters, repatriation assistance to their home regions using a Minutes of Handover, and economic empowerment programs in the form of skills training. However, the success of reintegration heavily depends on acceptance by the family and the social environment to mitigate the stigma of “failure.” The main obstacles identified include budget constraints for post-program monitoring and inaccurate address data for migrant workers. The implications of this study emphasize that reintegration strategies should not be limited to the administrative aspects of repatriation alone, but require strengthened cross-sectoral collaboration and adequate budgetary support for ongoing monitoring. This is crucial to ensuring the economic self-reliance of migrant workers in their home country and preventing them from returning to illegal migration due to social and economic pressures.